Quorum Sensing as a Trigger That Improves Characteristics of Microbial Biocatalysts - Elena Efremenko; Olga Senko; Nikolay Stepanov; Aysel Aslanli; Olga Maslova; Ilya Lyagin (Microorganisms, 2023)
Quorum sensing (QS) of various microorganisms (bacteria, fungi, microalgae) today attracts the attention of researchers mainly from the point of view of clarifying the biochemical basics of this general biological phenomenon, establishing chemical compounds that regulate it, and studying the mechanisms of its realization. Such information is primarily aimed at its use in solving environmental problems and the development of effective antimicrobial agents. This review is oriented on other aspects of the application of such knowledge; in particular, it discusses the role of QS in the elaboration of various prospective biocatalytic systems for different biotechnological processes carried out under aerobic and anaerobic conditions (synthesis of enzymes, polysaccharides, organic acids, etc.). Particular attention is paid to the biotechnological aspects of QS application and the use of biocatalysts, which have a heterogeneous microbial composition. The priorities of how to trigger a quorum response in immobilized cells to maintain their long-term productive and stable metabolic functioning are also discussed. There are several approaches that can be realized: increase in cell concentration, introduction of inductors for synthesis of QS-molecules, addition of QS-molecules, and provoking competition between the participants of heterogeneous biocatalysts, etc.).